Self-sufficiency of agriculture in Finland in 1970—1983 - Kettunen, Lauri (Agricultural and Food Science, 1986)
This study is aimed at considering self-sufficiency and food security in Finland. Self-sufficiency of final products has been over 100 % for a long period. Only self-sufficiency of fruits and vegetables is below 100 % due to the climate. Self-sufficiency of energy, protein and fat of the diet is also examined in this article. A new indicator of total self-sufficiency is developed by dividing the total yield measured in feed units with the total feed requirement of total human consumption, measured also in feed units. According to these calculations total self-sufficiency has been from 105 % to 130%, depending on the quantity of total yield. Itis difficult to make adequate calculations of self-sufficiency of inputs, since the industry producing agricultural inputs is operating under free trade, and tries to benefit from foreign trade. Imports of energy, raw materials, machines and implements lower self-sufficiency. Some estimates are, however, given in the text. The article also discusses the attempts to improve food security by storage. Agricultural research aims to clarify how alternative cultivation methods could lessen the dependence on imports, and thus improve the food security.